FENOMENA KEKERASAN SEKSUAL TERHADAP ANAK DI BAWAH UMUR BERDASARKAN PERSPEKTIF HUKUM KELUARGA (ISLAM ) DI INDONESIA - Susfita, Nunung (Universitas Islam Negeri Raden Fatah Palembang, 2018)
Sexual violence phenomenon to under age childerns have become a social problem started from national level untill international level. Because, untill now perecentage of this case numbers increased sharply in various regions or corners of indonesia. Childerns in under age are targeted both as perpetrators and victims on immoral behavior. One of the indicators, associated with the pattern of implementation of roles, rights and obligations parents to their children in family life. So, the outhor raises the theme of Sexual violence phenomenon to under age childerns based on islamic family law perspective in indonesia- (study case in Empang subdistrict regency of Sumbawa Besar).This research aims to analyze the sexual violence phenomenon to under age childern based on islamic family law in Empang subdistrict regency of Sumbawa Besar. This research uses a Normative-phenomenological aproach, the type is Qualititative-Deskriptive ( case study). Data sources are obtained through observation and interview methods. Based on the results of the research, it known there are several internal and ekternal factors underlying the occurrence of sexual violence phenomenon to under age childerns (study case in empang subdistrict regency of sumbawa besar), as like : a). Uncontrolled treatment and promiscuity from parents control. b). There’s no information, media, dissemination and counseling of the case received by childeren from school institution and goverment releted with impact and danger from sexual violence behavior. c). Lack of fungtion and role of basic aducation institution as counselors for childrens when they study at school and so on.